Sensitive impedimetric biosensor for direct detection of diazinon based on lipases - Zehani, Nedjla; Dzyadevych, Sergei V.; Kherrat, Rochdi; Jaffrezic-Renault, Nicole J. (Frontiers in Chemistry, 2014)
Two novel impedimetric biosensors for highly sensitive and rapid quantitative detection of diazinon in an aqueous medium were developed using two types of lipase, from Candida Rugosa (microbial source) (CRL) and from porcine pancreas (animal source) (PPL) immobilized onto a functionalized gold electrode. The lipase is characterized to specifically catalyze the hydrolysis of ester functions leading to the transformation of diazinon into diethyl phosphorothioic acid (DETP) and 2-isopropyl-4-methyl-6-hydroxypyrimidine (IMHP). The developed biosensors both presented a large wide range of linearity up to 50µM with a detection limit of 10 nM for the CRL biosensor and 0.1 µM for the PPL biosensor. A comparative study was carried out between the two biosensors and results showed higher sensitivity for the CRL sensor. Moreover, it presented good accuracy and reproducibility, and had very good storage and multiple use stability for 25 days when stored at 4°C.